Approach to calculating spatial similarity degrees of the same river basin networks on multi-scale maps. Issue 7 (8th August 2016) - Yan, Haowen; Shen, Yuzhong; Li, Jonathan
Abstract : Obtaining spatial similarity degrees among the same objects on multi-scale maps is of importance in map generalization. This paper firstly defines the concepts of 'map scale change' and 'spatial similarity degree'; then it proposes a model for calculating the spatial similarity degree between a river basin network at one scale and its generalized version at another scale. After this, it validates the new model and gets 16 points in the model validation process. The x -coordinate and y -coordinate of each point are map scale change and spatial similarity degree, respectively. Last, a formula for calculating spatial similarity degree taking map scale change as the only variable is obtained by the curve fitting method. The formula along with the model can be used to automate the algorithms for simplifying river basin networks.